2016
DOI: 10.1007/s11999-016-4704-8
|View full text |Cite
|
Sign up to set email alerts
|

Inaccuracies in the Use of Magnification Markers in Digital Hip Radiographs

Abstract: Background With the ubiquity of digital radiographs, the use of digital templating for arthroplasty has become commonplace. Although improved accuracy with digital radiographs and magnification markers is assumed, it has not been shown. Questions/PurposesWe wanted to (1) evaluate the accuracy of magnification markers in estimating the magnification of the true hip and (2) determine if the use of magnification markers improves on older techniques of assuming a magnification of 20% for all patients. Methods Betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 8 publications
4
46
0
8
Order By: Relevance
“…Whiddon and Bono18) reported that the use of radiographic size markers is encouraged to mitigate potential errors, and this marker provides an easy calculation of magnification because the actual measurement will correspond with the percentage of magnification. Whereas one recent study suggested that the use of magnification marker while taking preoperative radiographs of the hip may be unnecessary, as simply setting the software to assume a 20% magnification actually was more accurate5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whiddon and Bono18) reported that the use of radiographic size markers is encouraged to mitigate potential errors, and this marker provides an easy calculation of magnification because the actual measurement will correspond with the percentage of magnification. Whereas one recent study suggested that the use of magnification marker while taking preoperative radiographs of the hip may be unnecessary, as simply setting the software to assume a 20% magnification actually was more accurate5).…”
Section: Discussionmentioning
confidence: 99%
“…Previously many authors have emphasized the importance of preoperative templating in total hip arthroplasty (THA)1234). Benefits of preoperative templating include estimation of appropriate acetabular and femoral component sizing, appropriate restoration of preoperative offset, correction of leg length discrepancy (LLD), and anticipation of special componentry or techniques5). Moreover, the survival of an implant is critically dependent on understanding the biomechanical balance and ensuring the accurate alignment of the implant6).…”
Section: Introductionmentioning
confidence: 99%
“…Estudos que analisam radiografias para planejamento de artroplastia utilizam diferentes métodos de posicionamento e de marcadores sem justificar a escolha, posicionando entre as coxas ou ao nível do trocânter maior. 6,11,14,15,21 Gamble et al 8 não especificam a técnica do posicionamento, apenas indicam a região. Kosashvili et al 22 não utilizaram qualquer marcador e apenas padronizaram a magnificação em 115% para fins práticos, com pouca interferência no resultado final.…”
Section: Discussionunclassified
“…Essas dificuldades podem implicar na necessidade de realização de múltiplas radiografias para adequação do exame, podendo influenciar na calibragem: descentralização do feixe radiográfico para o lado que foi posicionado o marcador ou colocação do marcador em posição acima ou abaixo do nível do trocanter maior para não ser afastado lateralmente pelo coxim gorduroso posterolateral da coxa. Alguns autores 8,[10][11][12]21 analisaram a relação do peso e/ou índice de massa corpórea (IMC) com a magnificação radiográfica, sem identificar resultados significantes, entretanto, nesse estudo houve correlação considerada ruim desses fatores com a ausência do marcador no trocânter maior, podendo ser desconsiderada na prática.…”
Section: Discussionunclassified
“…The templating procedure has potential inherent flaws resulting from unknown radiographic magnification [ 4 ]. Preoperative radiographs could be performed with a magnification marker that allows scaling of the radiograph [ 5 ].…”
Section: Introductionmentioning
confidence: 99%